Crizotinib plus radiotherapy in brain oligoprogressive NSCLC ROS1 rearranged and PD-L1 strong - Occhipinti, Mario; Falcone, Rosa; Onesti, Concetta Elisa; Botticelli, Andrea; Mazzuca, Federica; Marchetti, Paolo; Lauro, Salvatore (Journal of Thoracic Disease, 2017)
ROS1+ patients represent a unique molecular subset of non-small cell lung cancer (NSCLC). Early phase clinical trials have shown a high response rate to crizotinib in these patients. We describe a case of an 18 years old woman, never smoker, with NSCLC ROS1+ and miliary brain metastases treated with crizotinib and radiotherapy. From October 2014 to June 2015 the Patient was treated with crizotinib. The first intracranial time to progression (IT-TTP) occurred after 7 months; the patient underwent stereotactic radiosurgery (SRS) and continued TKI treatment. The second IT-TTP appeared after 16 months. A continued response in the chest was observed for all the 23 months of crizotinib treatment. At the progression, we assessed programmed death ligand 1 (PD-L1) expression by immunohistochemistry, that resulted highly expressed. Our report indicates that the integration of crizotinib with local treatments should be considered in ROS1 NSCLC patients experiencing oligometastatic progression. Moreover, this case is an example of PD-L1 strong in oncogene addicted patients.